ADUBAÇÃO FOLIAR DO FEIJOEIRO. IV- EFEITOS DE DOSES E ÉPOCAS DE APLICAÇÃO DE NPKS - Rosolem, C. A.; Machado, J. R.; Kantack, R. A. D. (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO FOLIAR DO FEIJOEIRO. IV- EFEITOS DE DOSES E ÉPOCAS DE APLICAÇÃO DE NPKS